(untitled) - Sugimoto, Yoshio (Cambridge, UK, 2003)
An Introduction to Japanese Society remains essential reading for students of Japanese society. Internationally renowned scholar Yoshio Sugimoto uses both English and Japanese sources to update and expand upon his original narrative in this sophisticated yet highly readable text. This book explores the breadth and diversity of Japanese society, with chapters covering class, geographical and generational variation, work, education, gender, minorities, popular culture and the establishment. Updates include an exploration of the 'Cool Japan' phenomenon and the explosion of Japanese culture overseas. This edition also features the latest research into Japanese society, updated statistical data, and coverage of recent events including the 2011 earthquake and tsunami, and the change in government. Written in a clear and engaging style, An Introduction to Japanese Society provides an insight into all aspects of a diverse and ever-evolving contemporary Japan.
Keywords: Nhật Bản,Japan; Phong tục và đời sống xã hội,Social life and customs